Processos classificatórios na recepção, triagem e encaminhamento de crianças e adolescentes aos abrigos: permanências e mudanças após a ação civil pública - Orestes, Fabrício Mazzaron (2011)
This work is part of the theme of "under protection measure" under the Child and Adolescent Statute (CAS) and articulated in its Articles 98 and 101. The objective of this study is to understand the mechanisms that operate the flow classification of children and teenagers among the "doorways" and shelters in the city of São Paulo. To meet this goal we used two procedures: the analysis of public documents and production interviews. The documents were divided into the following categories: laws and statutes, policies and guiding plans and reports. The interviews were conducted in a shelter on the southern city of São Paulo that carries out service to the age group 0-17 years and 11 months. The professionals selected for interview in the team's technical service, namely, coordinator, psychologist and social worker. Amounted to three interviews prepared based on semi-structured methodology. The analysis of interviews and documents followed the methodology of discursive practices including language in the speech as action, ie, the modes from which the contents produce discursive sense about the social world. In addition, we worked with the perspective of Foucault developed the concepts of disciplinary mechanisms and security mechanisms to review processes and the classification in the flow between the shelters. From the analysis of the documents drawn up taking institutional flow as a criterion the time for each service they perform in the shelters. The arrangements were found for "short time" (up to two months) and "long time" (two years) for the realization of institutionalization, namely respectively the "gateways" and shelters. Comparison between the analysis of documents with the analysis of the interviews allowed us to recognize the practice of eligibility criteria that operate on the network from categories such as history on the streets, drug addiction, offense, mental health and age. These categories, acting alone or in combination, act as a filter and their effects imply classification provided better retention of children and adolescents in the "gateways" to the exclusion of the protection system formed by the network of shelters. These classificatory practices, especially in the categories analyzed, go against the principles of universality and integral protection doctrine advocated by the CAS because it reduces or negates the protection rights of children and especially teenagers who have a history of street drug addiction and infringement